Risiko Ketidakpatuhan Wajib Pajak Sebagai Dasar Peningkatan Kepatuhan - Santoso, Wahyu (Jurnal Trikonomika, 2009)
Risk-based approach has been used in audit-case selection to ensure that the audit is more focused on high risk taxpayers, non-compliance taxpayers, by which taxpayersâ compliance could be improved. To do so, a good understanding on variables determining taxpayersâ non-compliance becomes necessary. This study employs non-compliance determinants identified in previous researches, i.e. the economics theory of tax compliance. The objectives of this study are: (1) to categorize taxpayers based on their risks, low, medium or high; (2) to find whether there is any significant difference between the categories of taxpayersâ risks; (3) to identify variables that differentiate taxpayers in each risk category. Discriminant analysis employed in this study is able to construct discriminant functions that could be used to categorize taxpayers into three types of taxpayers based on their non-compliance risks, low-risk, middle-risk, and high-risk taxpayers so that the discriminant functions could predict whether a taxpayer tends to a low-risk, a middle-risk or a high-risk taxpayer. Moreover, the discriminant functions could be improved such that it could be used as a tool in risk-based approach applied in audit-case selection process. Hopefully, it can improve the effectiveness of tax audits and ends up with improved taxpayersâ compliance. This study identifies variables determining corporate taxpayersâ non-compliance. The variables are tax rate, penalty, tax audit, capital structure, the type of shareholders, the type of taxpayersâ business, taxpayersâ business scale, ratio taxes paid over sales and loss carry forward. The study also identifies dominant variables in each category of taxpayersâ risks.